Fiscal Decentralisation and Local Government Reform: Adaptation in Ukraine Experience of Poland and Lithuania - Borodina, O. (Економічний вісник Донбасу, 2023)
An effective local government system is one of the basic platforms for the functioning of the country in crisis conditions and the key to a successful post-war recovery of the economy at all levels. Studying the experience of European countries, primarily neighboring countries, greatly facilitates the construction of an optimal model of such a model. The article analyzes the fiscal innovations of Poland in detail, taking into account the identity of the administrative-territorial system and the identity of the formation of local self-government bodies. The indisputable advantage of the introduction of innovative fiscal regimes (Estonian СIT) for the economy of Poland has been established. The conclusions are convincingly illustrated by the dynamics of Poland's GDP growth and the rankings of Poland and the Baltic countries in the world rankings of tax capacity. The study of the experience of Lithuania in the field of reforming the territorial organization of power, carried out in the article, led to the ascertainment of revolutionary phenomena introduced by the neighboring country during both stages of administrative reform. Namely: the presence of a financial self-control mechanism implemented at the sub-regional level and an exceptional example of the delegation of powers from local self-government to a territorial unit managed by a civil servant (and not vice versa). Effective recommendations on borrowing Polish and Lithuanian experience and adapting it to modern conditions of Ukraine's development have been provided. It was established that dialogue with local civil society is the driving force behind the effectiveness of local self-government reform